Ductus Venosus Doppler S/D Value Adjusted Alfa Fetoprotein Levels to Decrease False Positive Rates - Alptekin Tosun; Enis Özkaya; Vakkas Korkmaz; Yasemin Çekmez (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: Fetal liver is mostly perfused by umbilical vein via ductus venosus and AFP is synthesized and secreted from fetal liver. In this study we tried to determine the effect of ductus venosus and umbilical blood flow on serum AFP levels STUDY DESIGN: Sixty women with 16-20 weeks of gestation were enrolled for the study. Subjects were divided into two: AFP levels lower (n=46) and higher than 2 MomS MoMs (n=14). All participants underwent serum AFP, ductus venosus and umbilical artery Doppler Doppler S/D screening. Effect of ductus venosus and umbilical artery blood flow on serum AFP levels were analyzed. RESULTS: Ductus venosus (AUC=0.945, P<0.001) and umbilical artery Doppler S/D (AUC=0.803, P=0.001) values were predictor for low AFP levels. In regression analysis, Ductus venosus Doppler S/D (Beta coefficient= -0.442, P<0.001) and umbilical artery S/D (Beta coefficient= -0.291, P=0.011) values were significantly associated with the AFP levels (R2=0.60). DV and umbilical artery Doppler S/D values adjusted serum AFP levels remained significant but mean value of AFP in group with AFP>2 MoM became 1.98 MoM after adjustment. CONCLUSION: Our study revealed that Ductus venosus and umbilical artery S/D value adjusted serum AFP levels may have lower false positive rates.